On cominimaxness of generalized local cohomology modules - Nguyen , Thanh Nam; Tran , Tuan Nam; Nguyen , Minh Tri (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
This research introduces and focuses on (I, M)-cominimax modules. The paper shows that if t is an nonnegative integer, M is a finitely generated projective R-module and N is an R-module such that is minimax and is (I, M)-cominimax for all then is minimax and is finite.